Implementation of Green Banking in the Largest Polish and Romanian Commercial Banks – An Analysis of Progress, Strengths, and Weaknesses - LEPCZYŃSKI, Błażej; SIEMIONEK-RUSKAŃ, Małgorzata; FANEA-IVANOVICI, Mina (Journal of Environmental Management and Tourism, 2023)
In the context of the Green Deal, which set out to transform Europe into a climate neutral area by 2050, governments and international bodies have shown a growing interest in the financing activities that contribute to this objective. This is because the financial system plays a crucial role in channelling resources towards less polluting technologies. Due to its central place in the financial system, the banking system has obviously taken on the same responsibility. Commercial banks can make a change towards a greener economy through the services they provide (green financial products), their loan portfolio (financing companies with a lower carbon footprint instead of highly polluting ones) and the internal transformation of their own activities (using renewable energies, less paper, etc.). The main aims of this paper are the assessment of the degree of development of green banking in Poland and Romania and the identification of weaknesses and strengths in the following areas: strategy, best examples of ESG (environmental, social governance) practices, ESG rating, methods to calculate and reduce the CO2 emissions, risk management, organization and management of a bank, financing the bank’s activities, credit activities (corporate banking and retail and mortgage banking). Using data from their reports and official websites, we find that steps have been made towards green banking, but progress is meagre, and the process is only in its early stages. This study will be useful to practitioners through the landmarks and set of criteria it proposes, as well as to researchers as a starting point for a deeper analysis of each area of green banking.